2017
DOI: 10.1007/s00425-017-2674-z
|View full text |Cite
|
Sign up to set email alerts
|

The hydroperoxide lyase branch of the oxylipin pathway protects against photoinhibition of photosynthesis

Abstract: This study describes a new role for hydroperoxide lyase branch of oxylipin biosynthesis pathway in protecting photosynthetic apparatus under high light conditions. Lipid-derived signaling molecules, oxylipins, produced by a multi-branch pathway are central in regulation of a wide range of functions. The two most known branches, allene oxide synthase (AOS) and 13-hydroperoxide lyase (HPL) pathways, are best recognized as producers of defense compounds against biotic challenges. In the present work, we examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Both values were consistent with our previously published data [40]. Additionally, the maximum quantum yield of PSII (F v /F m ), which indicates the maximum photochemical efficiency of PSII [55,56], was estimated. The obtained F v /F m values were the same for PSII from both WT and cia3 (Figure 4B) and was near 0.65.…”
supporting
confidence: 91%
“…Both values were consistent with our previously published data [40]. Additionally, the maximum quantum yield of PSII (F v /F m ), which indicates the maximum photochemical efficiency of PSII [55,56], was estimated. The obtained F v /F m values were the same for PSII from both WT and cia3 (Figure 4B) and was near 0.65.…”
supporting
confidence: 91%
“…All verified genes except HPL had higher expression level in flower than in leaf and scale. A very recent study revealed HPL involvement in protecting the photosynthetic apparatus [ 52 ]. We deduce that this gene may play an important role in lily leaf and further functional studies are required to understand its role in lily leaf and flower.…”
Section: Discussionmentioning
confidence: 99%
“…Unfavorable environmental conditions affect wheat crop yield globally [7]; therefore, the improvement of wheat tolerance to environmental stresses is of particular importance. The modification of individual steps of oxylipin biosynthesis pathway results in the alteration of plant tolerance to environmental challenges, as shown for Arabidopsis [8,9,10,11,12] and other species, including a few monocots [6,13,14]. For wheat, a protective effect of exogenously applied jasmonates under conditions of biotic and abiotic stresses was demonstrated in numerous studies [15,16,17], suggesting that the modulation of the activity of jasmonate-based signaling systems is a promising approach for the improvement of wheat tolerance to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%